Edukasi Tentang Pemberian Makanan Pendamping ASI - Fatihatul Hayati (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
Indonesia is included in the group of countries with a high prevalence of stunting (30-39%) where this prevalence increased from 36.8% in 2007 to 37.2% in 2013. According to UNICEF, the indirect factor causing stunting is parenting (ASI-Exclusive and ASI Complementary Foods/ MP-ASI) are not good. Several studies have suggested that nutritional problems in infants and children are caused by inappropriate breastfeeding and MP-ASI habits. Supplementary feeding for ASI 6-12 months of age is often a problem for families, generally families choose fast food, while self-cooking takes longer, this also occurs in the people of the Kotabaru sub-district area so education needs to be done to mothers who have babies less than 6 months old so they can prepare the right MP-ASI for their children later.